Neuroplastic changes following rehabilitative training correlate with regional electrical field induced with tDCS - Halko, M.A.; Datta, A.; Plow, E.B.; Scaturro, J.; Bikson, M.; Merabet, L.B. (NeuroImage (Orlando, Fla.), 2011)
Transcranial direct current stimulation (tDCS) has recently emerged as a promising approach to enhance neurorehabilitative outcomes. However, little is known about how the local electrical field generated by tDCS relates to underlying neuroplastic changes and behavior. To address this question, we present a case study analysis of an individual with hemianopia due to stroke and who benefited from a combined visual rehabilitation training and tDCS treatment program. Activation associated with a visual motion perception task (obtained by functional magnetic resonance imaging; fMRI) was used to characterize local changes in brain activity at baseline and after training. Individualized, high-resolution electrical field modeling reproducing precise cerebral and lesioned tissue geometry, predicted distortions of current flow in peri-lesional areas and diffuse clusters of peak electric fields. Using changes in fMRI signal as an index of cortical recovery, correlations to the electrical field map were determined. Significant correlations between the electrical field and change in fMRI signal were region specific including cortical areas under the anode electrode and peri-lesional visual areas. These patterns were consistent with effective tDCS facilitated rehabilitation. We describe the methodology used to analyze tDCS mechanisms through combined fMRI and computational modeling with the ultimate goal of developing a rationale for individualized therapy. ► Transcranial direct current stimulation is being used to enhance neurorehabilitative outcomes. ► Changes in fMRI signal were correlated with the electrical generated field map. ► Significant correlations were region specific. ► These patterns were consistent with effective tDCS facilitated rehabilitation.